Efforts To Improve Biology Learning Through Media Picture Of Student Class Xi Sma Negeri 6 Padang Lesson 2014-2015 - Deswaniar Deswaniar (Fakultas Sastra Universitas Ekasakti, 2018)
In learning to learn something well, we need to use our existing senses such as listening, seeing, and asking questions about material discussions with teachers or others. Not only that, teachers need to